New prospectives on light adaptation of visual system research with the emerging knowledge on non-image-forming effect - Wang, Shuxiao; Zhao, Jianping (Frontiers in Built Environment, 2022)
Light adaptation is very important to keep the visual system acutely sensitive to scene content over a wide range of illumination, and has strong influence on brightness perception, visual performance and glare evaluation. The estimation method for the light adaptation state under real circumstances is a big pending topic for lighting industry. The discovery of Intrinsically Photosensitive Retinal Ganglion Cells (ipRGCs) has offered us an exciting entry point to comprehend how light adaptation is regulated. In this paper, we made a comprehensive and thorough analysis of 45 studies focusing on light adaptation with the emerging knowledge on non-image-forming effect (NIF), to help researchers facilitate the research on light adaptation under complex luminance distribution. From the review, we can have the following outputs: 1) NIF may directly mediate the function of luminance adaptation, and its action spectrum may we can take pupillary light reflex (PLR) as an objective indicator for the adaptation; 2) the action spectra of light adaptation may not be a fixed formula like V(λ), but may vary dynamically with luminance level; 3) there is high necessity to conduct research on light adaptation within a natural and complex environment. All these outputs can provide us a new perspective on light adaptation in visual system research.